Evaluasi Penjadwalan Waktu dan Biaya pada Pembuatan Crude Storage Tank (600 Mb) Menggunakan Metode Critical Path Method - Ridwan, Muhamad; Supriyadi, Supriyadi; Wibowo, Tri Joko (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2016)
The company uses the Gantt Chart method for scheduling planning, but this method has several disadvantages, that is, it cannot explicitly indicate the relationship between activities and how one activity results in other activities if the time is late or accelerated. To determine the optimal duration and the total cost of building 1 (one) Crude Storage Tank capacity of 600 MB (Mega Barrel) an optimization of the duration of the project is needed so that it can be known how long a project is completed and looking for possible acceleration of project time using the Critical method Path Method is a method used to make project scheduling. By using the Critical Path Method method the work of building 1 (one) Crude Storage Tank with a capacity of 600 MB (Mega Barrel) on the Open Access (Phase-1) RU-II Dumai project, can be completed within a period of 384 days / 64 weeks, and trajectory critical lies in the b-c-d-e-f-j-l activity with a total cost of Rp.15,086,074,328.